Integrating biological control and host plant resistance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
This publication features the working group reports presented at the seminar on thematic, regional (Southern Africa, Eastern Africa, and West and Central Africa) and crop-centred (cowpea, cotton, coffee and cereals) issues.